A normalização da língua portuguesa no século XVIII e o verdadeiro método de estudar de Luís António Verney - Gonçalves, Maria Filomena (2009)
This article deals with the doctrine of Luís António Verney in the context of “linguistic normalization” registered in the eighteenth century. During this century, the observation of the various linguistic usages has led to an intense activity around the metalinguistic “norm” of the Portuguese language. The effort of standardization and regulation of the language could not fail to manifest itself in the True Method of Studying (1746), a reformist work par excellence, as shown in the particular orthography adopted by Verney or in his standardization of morphological and lexical uses. This article seeks to demonstrate that a rational method underlies Verney’s (meta)linguistic doctrine.